2017
DOI: 10.1007/s00520-017-3851-0
|View full text |Cite
|
Sign up to set email alerts
|

Guidance for establishing an integrative oncology service in the Australian healthcare setting—a discussion paper

Abstract: There is an obvious mismatch between the high reported rates of use of traditional and complementary medicines (T&CM) by Australian cancer patients and cancer survivors and the low numbers of Australian cancer services integrating T&CM. An estimated 65% of Australian cancer patients use at least one form of T&CM. Over half use T&CM in conjunction with conventional cancer therapy. Yet, less than 20% of Australian hospital cancer care facilities provide access to T&CM. This compares to around 70% of UK cancer ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…(15) Despite reports of relatively high use of integrative oncology, Australia is behind other western countries (e.g., US and UK) in providing access to integrative oncology via primary oncology treatment settings. (14,19,20) This is surprising since cancer survivors in 2017 make up 4% of Australia's population (more than one million). (21) This number is expected to increase to 1.9 million by 2040.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(15) Despite reports of relatively high use of integrative oncology, Australia is behind other western countries (e.g., US and UK) in providing access to integrative oncology via primary oncology treatment settings. (14,19,20) This is surprising since cancer survivors in 2017 make up 4% of Australia's population (more than one million). (21) This number is expected to increase to 1.9 million by 2040.…”
Section: Resultsmentioning
confidence: 99%
“…Further research is needed to support the role and effectiveness of integrative oncology in meeting the needs of cancer patients in Australia, as well as strategies to facilitate how to successfully and systematically integrate these practices into Australian cancer care. (19) Further research is also needed on the role that integrative oncology professionals play in referring cancer patients to other allied and medical professionals, to meet the physical and psychological concerns of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Project implementation also relates to the choice of CM. As has been suggested by others, 25,34 this project proposed to select CMs on the basis of specific criteria, including scientific evidence. In Switzerland, homeopathy, Traditional Chinese Medicine, anthroposophic medicine, and herbal medicine are the four CMs delivered by physicians who require specific training and meet federal standards.…”
Section: Assessment Of Current Practicementioning
confidence: 99%
“…36 However, integrative medicine is what should be provided in hospitals, especially in academic centers. Some studies have suggested improving CM literacy and education among hospital health care professionals 34 and 610 RODONDI ET AL.…”
Section: Assessment Of Current Practicementioning
confidence: 99%